PSIKOLOGI PENDIDIKAN ISLAM DALAM AL-QUR’AN - Asmira Efendi; Siti Rohimah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Abstracts are written in Indonesian and English using the typeface Book Antiqua 11 pt with single spacing. Abstract length is not more than 250 words. Avoid writing abbreviations, acronyms, or mathematical symbols in the abstract. Abstract of research results article contains brief background, objectives, methods, research results This paper explores the Qur'an's conceptual contributions to the development of Islamic educational psychology, particularly in the formation of learners' character and the optimization of their innate potential. It investigates how the Qur’an incorporates foundational psychological principles through three key educational approaches: spiritual motivation, prophetic exemplarity and behavioral habituation, and behavioral reinforcement via reward and punishment mechanisms. Employing a qualitative library research method, the study analyzes selected Qur'anic verses through the lens of educational psychology. The results indicate that Qur'anic motivation transcends material incentives, emphasizing a hereafter-oriented worldview. Prophetic role modeling and repeated righteous actions are shown to be effective in value internalization, while reinforcement through promised rewards and warned punishments is structured pedagogically and proportionately.  These findings affirm the Qur’an as a comprehensive source for the development of Islamic educational psychology.